Morphological and isozymic diversity of the cultivated yams (Dioscorea cayenensis/Dioscorea rotundata complex) of Cameroon - Mignouna, Hodeba D.; Dansi, A.; Zok, S. (2002)
Using IPGRI's descriptors, 45 accessions of Guinea yams (Dioscorea cayenensis Lam./ Dioscorea rotundata Poir. complex) collected in Cameroon were classified into six cultivar groups based on their morphological similarities. An identification key is proposed for the cultivar groups. Six enzymatic systems (6PGD, PGI, AAT, SKDH, PGM, EST) were also used to assess genetic variation within these cultivated yams. Twenty-eight genotypes were identified within the 45 accessions analysed. The clustering of accessions based on isozyme data is very close to the one obtained using morphological characters.